An Overview of Regular Dialysis Treatment in Japan (as of 31 December 2012). Issue 6 (December 2014) - Nakai, Shigeru; Hanafusa, Norio; Masakane, Ikuto; Taniguchi, Masatomo; Hamano, Takayuki; Shoji, Tetsuo; Hasegawa, Takeshi; Itami, Noritomo; Yamagata, Kunihiro; Shinoda, Toshio; Kazama, Junichiro James; Watanabe, Yuzo; et al.
Abstract A nationwide statistical survey of 4279 dialysis facilities was conducted at the end of 2012, among which 4238 responded (99.0%). The number of new dialysis patients was 38 055 in 2012. Since 2008, the number of new dialysis patients has remained almost the same without any marked increase or decrease. The number of dialysis patients who died in 2012 was 30 710; a slight decrease from 2011 (30 743). The dialysis patient population has been growing every year in Japan; it was 310 007 at the end of 2012, which exceeded 310 000 for the first time. The number of dialysis patients per million at the end of 2012 was 2431.2. The crude death rate of dialysis patients in 2012 was 10.0%, a slight decrease from that in 2011 (10.2%). The mean age of new dialysis patients was 68.5 years and the mean age of the entire dialysis patient population was 66.9 years. The most common primary cause of renal failure among new dialysis patients was diabetic nephropathy (44.2%). The actual number of new dialysis patients with diabetic nephropathy has been approximately 16 000 for the last few years. Diabetic nephropathy was also the most common primary disease among the entire dialysis patient population (37.1%), followed by chronic glomerulonephritis (33.6%). The percentage of dialysis patients with diabetic nephropathy has been continuously increasing, whereas not only the percentage but also the actual number of dialysis patients with chronic glomerulonephritis has decreased. The number of patients who underwent hemodiafiltration (HDF) at the end of 2012 was 21 725, a marked increase from that in 2011 (14 115). In particular, the number of patients who underwent on‐line HDF increased threefold from 4890 in 2011 to 14 069 in 2012. From the results of the facility survey, the number of patients who underwent peritoneal dialysis (PD) was 9514 and that of patients who did not undergo PD despite having a PD catheter in the abdominal cavity was 347. From the results of the patient survey, among the PD patients, 1932 also underwent another dialysis method using extracorporeal circulation, such as hemodialysis (HD) and HDF. The number of patients who underwent HD at home in 2012 was 393, a marked increase from that in 2011 (327).